The impact of initial credit ratingAnnouncement of bonds on stock prices: An analytical study in the Abu Dhabi Securities Market (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The purpose of the research is to investigate the response of stock prices of companies that issued debt instruments (bonds) listed on the Abu Dhabi Securities Exchange for information content from the Moody's first credit rating announcements for the period 1 January 2005 - 30 May 2017. The study methodology was used to verify the existence of this response by the market and the Market efficiency of the Semi-strong shape.  The research focused on testing the impact of the initial announcement.The research showed that there is an influential information content to announce credit ratings in stock prices, with different responses between negative and positive. It was also found that the industrial sectors sample research separately differ in their response to the announcement where the banking sector was more responsive than other sectors and most of the response was positive while the Real estate sector has a negative impact on the prices of its stock, The impact on stock prices led to extraordinary returns when the initial rating was announced, indicating that the Abu Dhabi market is not as efficient as the semi-strong. The study reached a number of recommendations, the most important of which was the need to enhance transparency and disclosure in order to enhance the efficiency of the financial markets, as well as encourage Iraqi companies to enter into the issuance of debt securities in order to finance their